The Effect of Arterial Oxygen Saturation on the Occurrence of Thrombocytopenia In Pediatric Patients with Tetralogy of Fallot - ERNY ERNY; OKKY PRASETYO; AYLI SOEKANTO (HANG TUAH MEDICAL JOURNAL, 2022)
Tetralogy of Fallot is one of the most common cyanotic CHD with the risk of hypoxia getting worse with increasing age of the patient. Thrombocytopenia is one of the consequences of chronic hypoxic conditions with a risk of bleeding. The purpose of this study was to determine the relationship between arterial oxygen saturation and thrombocytopenia in patients with tetralogy of Fallot. Research method: case control study, population of TF patients with thrombocytopenia and non-thrombocytopenia, measurements of age, arterial oxygen saturation and platelet count were performed. Multiple logistic regression was performed to determine the effect of arterial oxygen saturation on the incidence of thrombocytopenia in 94 TF patients. The results: from 94 TF populations divided into 47 thrombocytopenia populations and 47 non-thrombocytopenia populations, there was an effect of arterial oxygen saturation with the incidence of thrombocytopenia with p = 0.000 (meaningful). Conclusion: increasing patient age will cause chronic hypoxia and thrombocytopenia.